Giant Ranula of the Neck: Differentiation from Cystic Hygroma - Macdonald, Andre J.; Salzman, Karen L.; Harnsberger, H. Ric (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Occasionally, diving ranulas may attain large dimensions (giant ranula); gross involvement of the submandibular and parapharyngeal spaces makes differentiation from other cystic neck masses, particularly cystic hygroma, difficult. As diving ranula and cystic hygroma are managed with different surgical approaches, avoidance of this pitfall is critical. Our purpose was to review the imaging findings of giant ranula and compare them with those of cystic hygroma to define those features that are helpful in differentiating these different disease entities.METHODS: We conducted a retrospective review of all cases of ranulas that had been surgically treated at our institution in a 15-year period. These were compared with cases of cystic hygroma that involved the same anatomic regions. Images were analyzed for anatomic location and morphology, with specific attention paid to those characteristics that might assist differentiation. Giant ranula was defined as any ranula that significantly involved the paraphyngeal space in addition to the submandibular space.RESULTS: Six patients with giant ranula and fifteen patients with cystic hygroma were reviewed. All giant ranulas retained tapered communication with the sublingual space and were homogeneous, thin-walled, anatomically defined, fluid-containing masses. One infected lesion enhanced, and another previously operated lesion demonstrated mild septation. Cystic hygroma commonly did not communicate with the sublingual space and had features of lobulation, septation and heterogeneity. Additional involvement of spaces not typically involved by ranula further assisted differentiation.CONCLUSION: Although giant ranulas may superficially resemble cystic hygroma, several imaging features allow confident differentiation of these two entities.